2018 IEEE Winter Applications of Computer Vision Workshops (WACVW) 2018
DOI: 10.1109/wacvw.2018.00013
|View full text |Cite
|
Sign up to set email alerts
|

Generic Object Discrimination for Mobile Assistive Robots Using Projective Light Diffusion

Abstract: A number of assistive robot services depend on the classification of objects while dealing with an increased volume of sensory data, scene variability and limited computational resources. We propose using more concise representations via a seamless combination of photometric and geometric features fused by exploiting local photometric/geometric correlation and employing domain transform filtering in order to recover scene structure. This is obtained through a projective light diffusion imaging process (PLDI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Additionally, it can be observed that these algorithms are executed in real time. Regarding hardware characteristics, robotic platforms such as the following robots were used: PR2 [ 105 ], Toyota’s Human Support [ 107 ], Romeo 2 [ 106 ], Turtlebot 2 [ 98 ], and NAO [ 108 ].…”
Section: Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it can be observed that these algorithms are executed in real time. Regarding hardware characteristics, robotic platforms such as the following robots were used: PR2 [ 105 ], Toyota’s Human Support [ 107 ], Romeo 2 [ 106 ], Turtlebot 2 [ 98 ], and NAO [ 108 ].…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…This information was used for navigation planning. Additionally, Papadakis et al in [ 106 ] proposed the projective light diffusion imaging process (PLDI) algorithm for the ROMEO2 robot capable of recognizing domestic objects for navigation planning. The authors implemented joint bilateral filtering to reconstruct the RGB-D images and ignore pixels with invalid depth values.…”
Section: Algorithms Used For Objectsmentioning
confidence: 99%